2018
DOI: 10.1038/s41598-017-18944-0
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer potentiality of lignan rich fraction of six Flaxseed cultivars

Abstract: The objective of our study is to highlight the therapeutic effect and mechanism of action by which purified Flaxseed hydrolysate (PFH) which is a lignan rich fraction exerts its anticancer activity on a human breast cancer cell line (T47D) and in mice bearing tumor. HPLC analysis of PFH of six flaxseed cultivars had shown that PFH of the cultivar Giza 9 (PFH-G9) contains the highest concentration of SDG (81.64 mg/g). The in vitro cytotoxic potentiality of PFH’s of six flaxseed cultivars was screened against a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 42 publications
(41 reference statements)
3
37
0
Order By: Relevance
“…Thus highest antioxidant potential may be attributed to biosynthesis of these substrates in response to SA exposure. The mentioned polyphenols have been reported to break the oxidation chain reaction and quench free radicles . Our study is also in harmony with observations of , which reported that application of SA enhance antioxidant potential of Catharanthus roseus .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus highest antioxidant potential may be attributed to biosynthesis of these substrates in response to SA exposure. The mentioned polyphenols have been reported to break the oxidation chain reaction and quench free radicles . Our study is also in harmony with observations of , which reported that application of SA enhance antioxidant potential of Catharanthus roseus .…”
Section: Resultssupporting
confidence: 92%
“…Recently, anticancer, antimicrobial, anti‐diabetic, antioxidant, and anti‐inflammatory activities of flax have been explored . These therapeutic properties are credited to the biologically active ingredients (BAIs) biosynthesized in flax . Lignans and neo lignans are the major BAIs detected in flax .…”
Section: Introductionmentioning
confidence: 99%
“…In the other protocols and times of analysis the percentages of damage reduction ranged from 58.63 to 91.88% (Table 4). The data of the comet and the micronucleus demonstrate complementary antigenotoxic / chemopreventive actions and are corroborated in the literature that already indicate anticarcinogenic action 25,27 , antioxidant 25,26 and anti-inflammatory 26 for brown flaxseed. In addition, the literature mentions that dietary fiber has anticarcinogenic capacity that can increase intestinal transit facilitating the excretion of toxic products, improving the intestinal microbiota, inhibiting the chronic inflammatory process and the migration of cancerous cells in the colon 38 , as well as the capacity of adsorbers of mutagenic and / or carcinogenic agents of the enteric metabolic process 24,28 .…”
Section: Resultssupporting
confidence: 81%
“…The higher weight gain among those who consumed the flaxseed for longer (trend for the Brown flaxseed and a significant increase for the Pre+continuous group) reflects both the higher caloric intake, made possible by the constituents of the seed, for example, by the high lipid content 24 , the benefits it provides to the weakened organism. Among the bioactive compounds, they are also lignins, with anticarcinogenic, antiestrogenic, antiangiogenic and antioxidant properties 25 ; α-linolenic acid, with antioxidant, anti-inflammatory 26 and anticarcinogenic activity 27 ; and the food fibers turns, with anticarcinogenic capacity, that act through the adsorption of mutagenic and / or carcinogenic agents 28 . Thus, a nutritional demonstration of the flaxseed for health recovery and, consequently, promoted healthy increasing weight.…”
Section: Resultsmentioning
confidence: 99%
“…The EAC cells are mouse derived ascetic carcinoma cells which easily accepted in mice body with high transplantable efficacy, rapid growth and confirmed malignancy. The subcutaneous injection of EAC cells, results the development of solid tumor model in mice, which is selected in this study (Ezzat et al, 2018; Mishra et al, 2018). BLEA has evaluated for anti-tumor potency using EAC induced allograft tumor mice model, which showed significant inhibition of tumor growth progression, delayed the tumor associated death and increase the survival of tumor bearing treated mice.…”
Section: Discussionmentioning
confidence: 99%